Hubungan Risiko Bisnis dengan Financial Leverage - Bahgia, Saiful (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2023)
This study aims to test the relationship between business risk and financial leverage in manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. The data analysis method in this study uses multiple linear regression to predict the influence of independent variables. The population in this research is a manufacturing company listed on the Indonesia Stock Exchange from 2017 to 2021. The sampling method in this study is the purposive sampling method. The results showed a relationship between business risk and financial leverage; this shows that the higher the business risk, the higher the company's financial leverage, so the company will be more careful in using sources of funds from debt.